Seasonal Influence on the Diurnal Behaviours of the Indian Flying Fox (Pteropus medius) in Lucknow, India - Anjum, Km Naheda; Kumar, Vijay; Ali, Mehdi; Elangovan, Vadamalai (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study investigates the impact of seasonal changes on the diurnal behaviours of the Indian flying fox, Pteropus medius, at seven different roosting colonies in Lucknow, Uttar Pradesh, India. Behaviours of P. medius were categorized into roosting behaviour (hang relaxed, hang alert, wing droop, swivel, sleep), stationary actions (stretch, sniff, wing fan, yawn, wing flick), auto-grooming behaviour (general groom, wing groom), and locomotory behaviour (quadrupedal movement, bipedal movement). Seasonal influences on these behaviours were analyzed with respect to physical factors such as temperature (⁰C) and humidity (%). Roosting behaviour was the most frequently observed category, followed by stationary actions, grooming, and locomotion. During the summer, bats increase wing fanning and seek out dense canopies to stay cool. In contrast, during the winter, they prefer to roost at the tops of trees or in trees with less canopy cover, where they spread their wings to bask in the sun and reduce wing fanning. In the summer, bats are drawn to dense canopy trees like Mangifera indica (with a canopy width of 12.64±2.63), while in the winter, they opt for trees with sparser canopies such as Eucalyptus species (canopy width of 7.60±4.06) and Bambusa species (canopy width of 2.00±0.00). These seasonal behaviours emphasize the significant role of sunlight and temperature. Seasonal averages temperature and humidity were recorded as 32.07±2.49°C and 63.10±10.09% in summer, 29.55±1.86°C and 86.75±3.68% in rainy season, 24.92±2.29°C and 82.00±4.68% in monsoon, and 17.69±2.70°C and 78.65±7.41% in winter. A correlation matrix plot demonstrated significant behavioural associations, notably a high positive correlation between wing fanning and grooming. There were no significant differences in diurnal behaviours in male and female. However the several behaviour including hang alert, hang relaxed, wing fan, general groom, quadrupedal movement, swivel, and stretch differ among sexes. Regression analysis showed that higher summer temperatures increased wing fanning in both male (p=0.0348) and female (p=0.0362) bats for thermoregulation, and higher roost temperatures were marginally linked to reduced sleep time, suggesting higher energy expenditure. This study highlights the adaptive behaviours of P. medius in response to seasonal climatic variations, providing insights essential for the conservation of the species.